Integration of Industry 4.0 technologies in industrial manufacturing processes - Sousa, Marcio Rizonildo Aquino de (2024)
The integration of Industry 4.0 technologies into industrial production processes represents a significant evolution. This article explores the impact and benefits of this integration, showing how emerging technologies are revolutionizing traditional production methods. The methodology addresses the fundamental concepts of Industry 4.0, such as device interconnection, real-time data analysis, and intelligent automation, and examines specific technologies incorporated into manufacturing processes, such as the Internet of Things (IoT), Additive Manufacturing, Artificial Intelligence (AI), and Augmented Reality (AR). Case studies and practical examples illustrate the implementation of these technologies in various sectors, from precision parts manufacturing to mass production. Finally, the challenges and opportunities are discussed, as well as the future implications for the manufacturing industry. This article offers a view of the role of Industry 4.0 in industrial production processes, highlighting its importance for competitiveness and innovation in the digital world.